1996
DOI: 10.1007/bf00996304
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Co, Mn, Mg and Al with d(GCGTACGC): a spectroscopic study

Abstract: Spectroscopic study on the interactions of trace elements Co., Mn, Mg and Al with d(GCGTACGC) indicated the following: Al and Mg did not alter Tm values. Mn enhanced Tm at lower concentration and decreased it at higher concentrations. Interestingly Co at higher concentration elevated the Tm. These studies also showed lower concentrations of Mn displaced EtBr, whereas Al could displace it at higher ionic strength. Mg and Co displaced EtBr fluorescence at moderate concentrations. The binding constant values and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In general, metal ions such as Cu(II), Co(II), Mn(II) and Mg(II) bind to ds-DNA at both phosphate groups and base residues sites, and Al(III) binds to it at the former site. [36][37][38][39] Al(III) binding to ds-DNA at base residues sites was previously proposed by Karlik et al, 21 and testified to be the case by 27 Al NMR. 24 Our studies have shown that about 53.5% of Al(III) is probably binding to ds-DNA at phosphate groups sites, and the other 46.5% of Al(III) is kinetically united at base residues sites.…”
Section: Al(oh)3 Precipitation Analyzed By Icp-aes and Raman Spectramentioning
confidence: 85%
See 1 more Smart Citation
“…In general, metal ions such as Cu(II), Co(II), Mn(II) and Mg(II) bind to ds-DNA at both phosphate groups and base residues sites, and Al(III) binds to it at the former site. [36][37][38][39] Al(III) binding to ds-DNA at base residues sites was previously proposed by Karlik et al, 21 and testified to be the case by 27 Al NMR. 24 Our studies have shown that about 53.5% of Al(III) is probably binding to ds-DNA at phosphate groups sites, and the other 46.5% of Al(III) is kinetically united at base residues sites.…”
Section: Al(oh)3 Precipitation Analyzed By Icp-aes and Raman Spectramentioning
confidence: 85%
“…22,41 The 221 nm peak is due to the formation of a hydrogen bond. 37 The peaks at 245.6 and 274.2 nm are ascribed to the base pairs of ds-DNA. 42,43 After the addition of Al(III) from 5.0 × 10 -7 to 1.0 × 10 -5 M, the broad 274.2 nm peak inclined to shift to be more positive, and seemed to split to a shoulder peak at 281 nm.…”
Section: Al(oh)3 Precipitation Analyzed By Icp-aes and Raman Spectramentioning
confidence: 99%
“…It was earlier reported that Al did not alter the t m of DNA, and Mg was found to enhance the t m of genomic DNA [10]. Rajan et al [16] reported that Al did not alter the t m of the DNA sequence the metal ions as well as the base sequence of the DNA. The divalent metal ions Mg, Mn and Co with, relatively small ionic radii, strongly interact with the DNA [16].…”
Section: D(gcccatgggc)mentioning
confidence: 98%
“…Rajan et al [16] reported that Al did not alter the t m of the DNA sequence the metal ions as well as the base sequence of the DNA. The divalent metal ions Mg, Mn and Co with, relatively small ionic radii, strongly interact with the DNA [16]. Although these metals are required for a number of biological functions, at higher concentrations they are reported to change the handedness of DNA [1-6].…”
Section: D(gcccatgggc)mentioning
confidence: 98%
See 1 more Smart Citation